2012
DOI: 10.1055/s-0032-1309774
|View full text |Cite
|
Sign up to set email alerts
|

Fully covered self-expanding metal stents for refractory pancreatic duct strictures in chronic pancreatitis

Abstract: Fully covered self-expanding metal stents (FC-SEMSs), which can be removed from the bile duct, have recently been used in the main pancreatic duct (MPD) in chronic pancreatitis. The aim of this study was to investigate the feasibility, safety, and efficacy of FC-SEMSs in painful chronic pancreatitis with refractory pancreatic strictures. The primary endpoints were technical success and procedure-related morbidity. Secondary endpoints were pain relief at the end of follow-up and resolution of the dominant pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 7 publications
3
50
1
1
Order By: Relevance
“…7,11,12,20,25,27,28,30,31 Although much variation exists between studies, the most common adverse events described include periprocedural pancreatitis, cholangitis, pain, secondary strictures, and stent migration. Stent migration is discussed separately in the following.…”
Section: Safety and Removabilitymentioning
confidence: 99%
“…7,11,12,20,25,27,28,30,31 Although much variation exists between studies, the most common adverse events described include periprocedural pancreatitis, cholangitis, pain, secondary strictures, and stent migration. Stent migration is discussed separately in the following.…”
Section: Safety and Removabilitymentioning
confidence: 99%
“…Several studies have shown the efficacy of endotherapy in patients with CP and PD strictures (Table 21.1) [16,[20][21][22][23][24][25][26][27][28][29]. Early series with a single plastic stent (PS) ± stricture dilation reported good short-term pain relief (70-94%).…”
Section: Results Of Ercp In Pd Stricture Managementmentioning
confidence: 99%
“…During a median follow-up period of 38 months, 84% of patients were pain-free after stent removal. The placement of a self-expandable metal stent (SEMS) has been reported in an attempt to maintain PD patency for a long term and reduce the number of interventions required for benign stricture management [27][28][29][30]. In a study from Brussels with SEMS placement for benign PD obstruction, 20 patients treated with uncovered SEMS (USEMS) had immediate pain relief [30].…”
Section: Results Of Ercp In Pd Stricture Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Other emerging indications for the use of FC-SEMS are (but not limited to) post-sphincterotomy bleeding, esophageal variceal bleeding, sealing of a perforation or bile leak and lately treatment of symptomatic biliary and pancreatic duct strictures. 4,5 Temporary placement of FC-SEMS can also be used to treat benign non-obstructive conditions in the GI tract, such as oesophageal and colonic fistulas. 6 In recent years, endoscopic ultrasound (EUS) has emerged as a mainstream therapeutic modality for drainage and fine-needle injection.…”
Section: Introductionmentioning
confidence: 99%